Pengaruh Digital Marketing Terhadap Keputusan Konsumen Dalam Membeli Produk Hidroponik Melalui Platform Media Sosial - Fauzia, Lily; Septiyana, Anjeli; Jufri, Mohammad; Darus, Mozard Bahauddin; Pebriyani, Dian (Universitas Galuh, 2024)
Hydroponics farming is an urban farming system that is being developed and marketed through social media.. The phenomenon that occurs is that hydroponic vegetables purchased via social media tend to be more expensive than those purchased directly due to shipping costs, however there are some consumers who choose to switch their purchases from conventional to online. The purpose of this study are to analyze the types of digital marketing platforms that are most widely used by consumers in purchasing hydroponic vegetable products at Binjai Hydroponics and to analyze the relationship between purchasing motivation, product quality, promotion, trust and perceived ease with consumer decisions in purchasing hydroponic vegetable products through online shopping at Hydroponics Binjai . The determination of Binjai Hydroponics, East Binjai District as the research location was determined purposively, because Binjai Hydroponics is the only hydroponic business that has marketed its products through social media in East Binjai Distict. Sampling method using Snowball Sampling, with a sample size of 60. The sample units used are consumers who have purchased Binjai Hydroponics Vegetables through online shopping. The method used in this research is descriptive qualitative analysis and Spearman’s rank test. The results of the analysis show that the type of Digital Marketing media platform most used by consumers in purchasing vegetable products at Binjai Hydroponics is Social Media W as many as 28 people or 46,7% and purchase motivation, product quality, promotion, trust and perceived ease have a significant correlation (relationship) with consumer decisions in buying hydroponic vegetable products through online shopping. Purchasing motivation has a low relationship strength, Product quality and promotion have a strong relationship strength, Trust and Perceived ease have a medium relationship strength.